Revisiting the geographical extent of exceptional warmth in the early paleogene Southern Ocean - Frieling, Joost; Bohaty, Steven M.; Cramwinckel, M. J.; Gallagher, S. J.; Holdgate, G. R.; Reichgelt, T.; Peterse, F.; Pross, Jörg; Sluijs, A.; Bijl, P. K. (Paleoceanography and paleoclimatology, 2023)
To assess zonal temperature and biogeographical patterns in the Southern Ocean during the Paleogene, we present new multi-proxy air- and sea-surface temperature data for the latest Paleocene (∼57-56 Ma) and the Paleocene-Eocene Thermal Maximum (PETM; ∼56 Ma) from the northern margin of the Australo-Antarctic Gulf (AAG). The various proxy data sets document the well-known late Paleocene warming and, superimposed, two transient late Paleocene pre-cursor warming events, hundreds of kyr prior to the PETM. Remarkably, temperature reconstructions for the AAG and southwest Pacific during the latest Paleocene, PETM and Early Eocene Climatic Optimum (∼53-49 Ma) show similar trends as well as similar absolute temperatures east and west of the closed Tasmanian Gateway. Our data imply that the exceptional warmth as recorded by previous studies for the southwest Pacific extended westward into the AAG. This contrasts with modeling-derived circulation and temperature patterns. We suggest that simulations of ocean circulation underestimate heat transport in the southwest Pacific due to insufficient resolution, not allowing for mesoscale eddy-related heat transport. We argue for a systematic approach to tackle model and proxy biases that may occur in marginal marine settings and non-analog high-latitude climates to assess the temperature reconstructions.
Zuerst veröffentlicht: 16. Februar 2023
Gesehen am 25.07.2023